PENERAPAN MODEL PEMBELAJARAN CTL PADA MATERI BILANGAN BERPANGKAT KELAS X SMK - Serafina Jenia; Lailatul Mubarokah; Risdiana Chandra Dhewy (LPPM STKIP PGRI Sidoarjo, 2022)
To make it easier to understand in learning mathematics, it is necessary to be related to the daily activities of students. As applied to the material of ranked numbers in this study. The purpose of this study is to explore what activities teachers and students do in CTL learning, knowing learning outcomes and student responses. The results of the study will be described descriptively with a quantitative approach. . The research was conducted at SMK PGRI 1 Sidoarjo class X TKJ. The number of learners in a class is 34 people. The result of the data analysis carried out was the ability of teachers to manage CTL learning on ranked number material obtained a value of 4.00 which is included in the very active criteria. The activities of students during the learning process can already be said to be active, because of the 34 students 26 active criteria and 8 are still less active criteria because they did not participate in the first meeting. The learning outcomes of class X TKJ students after taking the ranking number question test are said to be complete because the percentage of completeness of learning outcomes reaches 88.23%. The response of students is said to be positive because all items of the statement fall into the category of very positive and positive, so the response of students is said to be positive. So that the application of the CTL learning model can be said to be effective.